Human Metapneumovirus Infection Plays an Etiologic Role in Acute Asthma Exacerbations Requiring Hospitalization in Adults - Williams, John V.; Crowe, James E.; Enriquez, Rachel; Minton, Patricia; Peebles, R. Stokes; Hamilton, Robert G.; Higgins, Stanley; Griffin, Marie; Hartert, Tina V. (The Journal of infectious diseases, 2005)
We determined the prevalence of human metapneumovirus (hMPV) infection in adults with asthma who were prospectively enrolled after hospitalization for an acute asthma exacerbation. Nasal wash specimens collected at admission and 3 months after discharge were tested for hMPV by real-time reverse-transcription polymerase chain reaction assays. hMPV was detected in 7 (6.9%) of 101 subjects at hospitalization and in 1 (1.3%) of 75 subjects at follow-up (odds ratio, 7 [95% confidence interval, 0.9–312]; P=.03). None of the patients with hMPV infection at hospitalization tested positive at follow-up, strongly suggesting that hMPV plays a direct etiologic role in acute asthma exacerbations